Legal Framework for Establishing Regional Planning Authority for Malaysia - Maidin, Ainul Jaria (Sweet & Maxwell Asia, 2011)
The idea that local authorities should be the ones determining the affairs of their local authority areas is an engrained rule in the structure of the Malaysian style of government. Historically, the local government has been responsible for shaping the development of urban and rural land use, transportation plans and various other land development issues within the boundary of its local authority areas. Recently, concepts such as “smart growth”, “new regionalism”,“new urbanism” or “metropolitan planning” have been gaining prominence amongst planners globally and appear to be challenging the local authority’s decision-making powers. Regional planning has gained prominence since it promotes effective and efficient use of resources and reduces regional imbalances and poverty, and achieves sustainable development. The Malaysian legislature has provided for the legal framework for establishing regional planning authority principally for purposes of promoting sound growth in many regions in the country. This paper seeks to analyse the related provision and the challenges posed to the government in establishing a regional planning authority and make suggestions to overcome such challenges.